Effects of ribwort plantain (Plantago lanceolata) extract on blood parameters, immune response, antioxidant enzyme activities, and growth performance in rainbow trout (Oncorhynchus mykiss) - Elbesthi, Randa Taher A; Özdemir, Keriman Yürüten; Taştan, Yiğit; Bilen, Soner; Sönmez, Adem Yavuz (Springer Science and Business Media LLC, 2020)
In this study, we examined changes occurred in blood parameters, immune responses, antioxidant enzyme activities, and growth performance of rainbow trout (Oncorhynchus mykiss) administered with ribwort plantain (RP) through feed. Fish (mean weight 36.56 ± 1.99 g) were fed a diet supplemented with an aqueous methanolic extract of RP at variable doses, 0 (control), 1 (RP1), 2 (RP2), and 3 g kg-1 (RP3) for 90 days. The final weight, weight gain, and specific growth rate were significantly increased in RP1, RP2, and RP3 treatment groups compared to that of the control. Among examined blood parameters, hemoglobin value in RP1 group (9.77 ± 0.10 g dl-1) only was significantly high on the 30th day of the study. When immune response parameters were evaluated, we observed that oxidative radical production and lysozyme activities were affected positively in experimental groups (P < 0.05). The highest oxidative radical production was determined in fish of RP3 group. Glutathione peroxidase and glucose 6 phosphate dehydrogenase were increased in RP3 group compared to control and other treatment groups. Based on these results, it is concluded that ribwort plantain promotes growth, enhances immune responses and antioxidant enzyme activities in rainbow trout, and therefore, may be used in aquaculture.
Keywords: Erythrocyte Indices; Glutathione Peroxidase; Plant Extracts; Superoxide Dismutase; Aquaculture; Glucosephosphate Dehydrogenase; Catalase; Animal Feed; Gas Chromatography-Mass Spectrometry; Hemoglobins; Hematocrit; Liver; Oncorhynchus mykiss; Erythrocyte Count; Animals; Food Additives; Oxidation-Reduction; Plantago; 3. Good health